PREVALENSI ASMA BRONKIAL ATOPI PADA PELAJAR DI DESA TENGANAN - Sastrawan, I Gede Pande; Suryana, Ketut; Ngurah Rai, I B (journal of internal medicine, 2012)
Asthma as one of the allergic diseases continuos to be a major public health problem in developed and developing countries. We carried out a population-based survey to search the prevalence of atopic asthma in school children of Tenganan, Manggis-Karangasem. Asthma was diagnose by quisioner and bronchodilator test. Atopic asthma define as asthma patients with total IgE > 100 IU/ml and or skin prick test 3 mm. Five hundred fourteen (91.5%) students out of of 562 students were were invited, participated the study. Thirty six (7%) students were diagnosed asthma based on peak expiratory flow variability after brochodilator test, stratified by sex there were 13 (36.1%) boys and 23 (63.9%) girls and 9 (25.0%) primary school children, 14 (38.9%) junior high, 13 (36.1%) high school, respectively. Mean of age, serum IgE total and wheal diameter was 13.42 ± 3.26 year, 1551.83 ± 2008.19 IU/ml, 22.9±3.4% and 3.58 ± 0.99 mm, respectively. Out of 36 asthma patients, 35 (97.2%) diagnosed atopic asthma consist of 12 (34.3%) boys and 23 (65.7%) girls, and 1 (2.8%) diagnosed nonatopic asthma.
Keywords: asthma, atopic asthma, prevalence